Use of Learning Management Systems in Learning Efforts during a Pandemic - Wiratomo, Yogi; Mulyatna, Fauzi (Universitas Negeri Surabaya, 2020)
This study aims to describe learning process that is suitable to be applied during a pandemic and learning outcome in form of learning media that are effective, practical, easily obtained, economic and easily understood by university students in receiving material. As class setting (online learning) is 8th semester lecture in the ICT-Based Mathematics Learning Media course using action research method. This research design used 3 cycles, with each cycle passing through the plan-act-observe-reflect stage. Data collection technique is by using observation related to the skills of designing and developing simple math learning applications based on android. Research data analysis was carried out based on: (1) initial ability analysis; (2) reflection related to the online learning process (3) learning outcomes. The conclusions of this study are: (1) distance learning during a pandemic is to implement simple application and to use clear tutorial; (2) learning outcomes in the form of learning media with Android-based applicationsKeywords: LMS, Action Research, Pandemic